To the possibility of detecting the "coronary theft" syndrome in small laboratory animals - I. B. Tsorin; S. A. Simonenko; M. B. Vititnova; S. A. Kryzhanovskiy (LLC "Publisher OKI", 2022)
The purpose of the study. There are investigation of the possibility of using the laser Doppler flowmetry method to assess blood microcirculation and analyze the mechanisms of its regulation in conditionally intact and ischemic myocardium in small laboratory animals (rats) to identify the "coronary theft" syndrome. Materials and methods. The experiments were carried out on white mongrel anesthetized (urethane 1300 mg/kg /b) male rats weighing 200-250 g. 28 days after the reproduction of an experimental myocardial infarction in an open chest and artificial lung ventilation, the microcirculation level was assessed in conditionally intact and ischemic areas of the myocardium by laser Doppler flowmetry. Using spectral wavelet analysis, the amplitudes of microcirculation oscillations normalized to the total perfusion associated with various regulation mechanisms were determined. Results. It was found that the microcirculation level is significantly lower in the ischemic zone of the myocardium compared with the conditionally intact one (17.3±2.8 and 30.3±1.3 per. units, respectively, p = 0.006, n = 8). Spectral wavelet analysis showed that in the ischemic injury zone, in comparison with the conditionally intact myocardium, the amplitudes of microcirculation oscillations normalized to the general level of microcirculation increase for all regulatory mechanisms. Conclusion. The laser Doppler flowmetry method can be used to assess the intensity of microcirculation in conditionally intact and ischemic myocardium. Using this method makes it possible to identify the "coronary theft" syndrome in experiments on small experimental animals.